Pengaruh Literasi Keuangan Syariah, Religiusitas, dan Pendidikan terhadap Pemahaman Riba pada Produk Mikro Syariah di Desa Kaligede, Tuban - Wahyu Qomariatul, Khoiriyah (Program Studi Ekonomi Syariah STAI Senori Tuban, 2025)
The Islamic finance industry in Indonesia has experienced significant growth over the last few decades. However, this growth has not been accompanied by increased public understanding of sharia principles, especially regarding riba in microfinance products. This is a challenge in increasing Islamic financial literacy and inclusion, especially in rural areas such as Kaligede Senori Tuban Village, where public understanding of riba remains low, possibly due to limited Islamic financial literacy, religious awareness, and educational levels. The purpose of this study is to determine the influence of Islamic financial literacy, religious awareness, and education level on the understanding of riba of sharia microfinance products. This study uses a quantitative approach, employing a survey method with an online questionnaire distributed to 35 housewives in Kaligede Village. The data obtained was then analyzed using multiple linear regression with the help of SPSS 16.0 software. In this study, it was found that: First, the variable of Sharia Financial Literacy has a t-calculation value of 2.718 > t-table of 2.040 and a significance value of 0.011 < 0.05. Second, the Religiosity Awareness variable has a t-count value of 0.212 < t-table of 2.040 and a significance value of 0.833 > 0.05. Third, the Education Level variable has a t-count value of 0.964 < t-table of 2.040 and a significance value of 0.342 > 0.05. Fourth, simultaneously, the variables of Islamic financial literacy (X1), awareness of religiosity (X2), and education level (X3) had a significant effect on the understanding of usury of Islamic microfinance products (Y) with an F-calculation value of 4.913 > f-table of 2.90 and a significance value of 0.007 < 0.05. Fifth, Islamic financial literacy is the most dominant variable in influencing public understanding of riba, with a beta value of 0.449.